Hydrochemical Characteristics and Groundwater Quality Assessment Using an Integrated Approach of the PCA, SOM, and Fuzzy c-Means Clustering: A Case Study in the Northern Sichuan Basin - Yao, Rongwen; Yan, Yuting; Wei, Changli; Luo, Ming; Xiao, Yong; Zhang, Yunhui (Frontiers in Environmental Science, 2022)
Groundwater is the precious resource that is of vital for human life. Widespread human activities occur in the Sichuan basin due to befitting climate and geological conditions, which inducing a series of groundwater contamination. In this paper, hydrochemcial analysis, principal component analysis (PCA), self-organization map (SOM) and fuzzy c-means clustering (FCM) were integrated for revealing the hydrochemical process and assessing groundwater quality in the northern part of the Sichuan basin, based on the collection of 203 groundwater samples. The groundwater hydrochemical types was dominated by HCO3-Ca type. The PCA results showed both natural and anthropogenic contributed to hydrochemical compositions. The combination of the SOM and FCM classifies neurons into two categories, the first category in which NO2- and NH4+ are the most similar, perhaps as anthropogenic sources of pollution, which have serious threats to human health. In the second category, total dissolve solids, Ca2+, Na+, Cl-, SO42, Mg2+, and K+ are the most similar, explained as the influence of natural factors. Ion source was determined by water-rock interaction: Na+ mainly comes from the dissolution of silicate rocks, Ca2+, Mg2+, HCO3- from the dissolution of calcite and dolomite. Cation exchange was recognized the water-rock interaction. The achievements would provide a significant reference for groundwater protection in the Sichuan Basin.